Cardiovascular effects of dipeptidyl peptidase-4 inhibitors in diabetic patients: A meta-analysis. (15th February 2015) - Savarese, Gianluigi; Perrone-Filardi, Pasquale; D'Amore, Carmen; Vitale, Cristiana; Trimarco, Bruno; Pani, Luca; Rosano, Giuseppe M.C.
Abstract: Background: Dipeptidyl peptidase-4 inhibitors (DPP-4is) improve glucose control in patients with type 2 diabetes mellitus (DM); however, only few studies were properly designed to evaluate their cardiovascular (CV) effects. The purpose of this study was to assess the impact of DPP-4i treatment on CV morbidity and mortality. Methods: Randomized clinical trials enrolling more than 200 patients, comparing DPP-4 versus placebo or active treatments in patients with DM and reporting at least one event among all-cause and CV mortality, myocardial infarction (MI), stroke and new onset of heart failure (HF) were included in the analysis. Results: Ninety-four trials enrolling 85, 224 patients (median follow-up = 29 weeks) were included in the analysis. Compared to control, treatment with DPP-4i did not affect all-cause and CV mortality, as well as stroke, in the short and long terms (< and >= 29 weeks, respectively). DPP-4i reduced the risk of MI in the short (RR: 0.584 [95% CI: 0.361 to 0.943]; p = 0.028), but not in the long term. Additionally, long-term treatment with DPP-4 was associated with a 15.8% increased risk of HF (RR: 1.158 [CI: 1.011 to 1.326]; p = 0.034). No heterogeneity among studies or publication bias was detected. Conclusions: DPP4is do not affect all cause- and CV-mortality and stroke in diabetic patients; the reduction in MI observed with short-term treatment does not persist in the long term. Long-term use of DPP-4i in diabetic patients is associated with increased risk of HF. Highlights: DPP-4i did not affect all-cause and CV mortality and stroke in the long and short terms. DPP-4i reduced the risk of MI in the short but not in the long term. Long term treatment with DPP-4 was associated with a 15.8% increased risk of HF.